Recommendations for Perioperative Prophylaxis of Venous Thromboembolism in the Adult Patient. National Multidisciplinary Consensus 2014 - Amaral, Cristina; Reis, Jorge; Guimarães, Luís; Sá, Ana Caronia; Moreto, Ana; Araújo, Fernando; Guimarães, Mariana; Felicíssimo, Paulo; Teixeira, José; Fonseca, Cristiana; Miranda, Lina (Journal of the Portuguese Society of Anesthesiology, 2014)
The purpose of these recommendations is to provide a community based on current scientific evidence tool, patient-centered, which may be useful in clinical practice and contribute to the appropriate, systematic and cross-implementation of prophylaxis of venous thromboembolism in the adult patient. With the support of the Portuguese Society of Anesthesiology were approved by National Multidisciplinary Consensus between specialties: Anesthesiology, Cardiology, Cardiothoracic Surgery; General Surgery - Bariatric Surgery; Aesthetic, Plastic and Reconstructive Surgery; Vascular Surgery; Gynecology and Obstetrics; Immuno-Haematherapy; Neurosurgery; Oncology; Orthopedics and Urology. Venous thromboembolism is a serious public health problem. In perioperative venous thromboembolic risk associated with individual factors of the patient, type of surgery, type of anesthesia and length of stay. Previous venous thrombosis, oncologic disease, advanced age, major orthopedic surgery, bariatric surgery and immobilization in bed, are some of the risk factors for thromboembolic events. The neuraxial blockade is associated with reduction in these events. The ENDORSE study evaluating the international implementation of the recommendations of the 7th Consensus of the American College of Chest Physicians on venous thromboembolism prophylaxis in Portugal, revealed that the rate of appropriate prophylaxis in the surgical patient at risk was inferior to many other European countries. In this study, among patients who have been prescribed thromboprophylaxis, some did not meet indication criteria, being exposed to unnecessary risks. The gaps identified in the prophylaxis of venous thromboembolism are related to the lack of effective inter-disciplinary communication, ignorance of recommendations and pharmacokinetics and pharmacodynamics of agents and the fear of bleeding complications. The lack of risk assessment models validated and easy to apply has hampered the standardization of criteria. These recommendations consider the Caprini risk assessment model. The assessment of the risk of venous thromboembolism is indicated to all offered surgery patients and should be recorded in the clinical process. Thromboprophylaxis is a multidisciplinary responsibility, should be based on a consideration of the risks of venous thromboembolism and bleeding and take into account the patient's values and preferences. The thromboprophylaxis should begin 6-12 hours after surgery (with exceptions).